Pelatihan Komunikai Bahasa Inggris Bagi Anak-Anak Panti Asuhan Nur Sholeh Melalui Metode Diskusi - Sriwana Ana; Sebastianus Torino Shandri; Melisa Walay (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service aims to help the orphanage's children develop their communication, especially in English communication. This service was carried out for children in the Nur Sholeh orphanage with 15 children participating. This method of community service uses the discussion method. From all the implementation of activities, this community service got satisfactory results where the use of this method had a positive impact on the training participants. Through this activity, the children of the orphanage are eager to communicate, especially in communicating using English both in taking part in discussions and practicing English communication as a medium of communication.